2022
DOI: 10.1039/d2cp03395j
|View full text |Cite
|
Sign up to set email alerts
|

Toward highly efficient hyperfluorescence-based emitters through excited-states alignment using novel optimally tuned range-separated models

Abstract: Several variants of optimally tuned range-separated hybrids are designed and validated for a reliable description of the excited-states alignment in the hyperfluorescence mechanism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 135 publications
(285 reference statements)
0
2
0
Order By: Relevance
“…The presence of a and b parameters provides more flexibility to examine the effects of the exchange contributions at the SR and LR parts on different properties. [52][53][54][55][56][57][58][59][60][61][62][63][64] Finally, because the governing parameters for the limiting behavior of the HF exchange tend toward a/r for r -0 and toward (a + b)/r for r -N, the constraint a + b = 1 needs to be fulfilled to recover the correct asymptotic limit, 1/r.…”
Section: Theoretical Aspectmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of a and b parameters provides more flexibility to examine the effects of the exchange contributions at the SR and LR parts on different properties. [52][53][54][55][56][57][58][59][60][61][62][63][64] Finally, because the governing parameters for the limiting behavior of the HF exchange tend toward a/r for r -0 and toward (a + b)/r for r -N, the constraint a + b = 1 needs to be fulfilled to recover the correct asymptotic limit, 1/r.…”
Section: Theoretical Aspectmentioning
confidence: 99%
“…The recent studies have revealed that regardless of the DFAs used during the optimal tuning of the range-separation parameter, generalized gradient approximations (GGAs) or meta-GGAs, almost similar optimal values of m are obtained. 54,55,57,[60][61][62][63][64]80,81 Accordingly, the widely used GGA, namely Becke-Lee-Yang-Parr (BLYP), 82,83 has been employed as the exchange and correlation terms during all the optimal tuning processes. However, in order to check the transferability of the obtained results and examine their dependency to the underlying DFAs, applicability of other DFAs, namely Perdew-Burke-Ernzerhof (PBE) 84 GGA and Tao-Perdew-Staroverov-Scuseria (TPSS) 85 meta-GGA, was also assessed.…”
Section: Computational Detailsmentioning
confidence: 99%